Constructing environmental responsibility in Saudi University policies: A critical discourse analysis of agency, modality, and accountability - Alowayyid, Norah Nasser Saleh; Ibrahim, Khaled Ahmed Abdel-Al; Ali Doum, Hamed Mohammed; Khan, Aayesha Sagir (Research Journal in Advanced Humanities, 2026)
A university can install solar panels, publish a Sustainable Development Goals report, and still leave basic questions unanswered: Who must act? Whose knowledge shaped the target? How will progress be judged, and what happens if the institution falls short? Environmental sustainability is therefore not only technical or managerial; it is also made governable through language. This article examines how Saudi universities construct environmental responsibility through intertextuality, evaluation, agency, modality, and stakeholder voice. It combines a critical synthesis of Saudi and international scholarship with an exploratory analysis of six English-language institutional texts published by King Abdullah University of Science and Technology, King Fahd University of Petroleum and Minerals, and the University of Tabuk. The framework integrates Fairclough's critical discourse analysis, van Leeuwen's social-actor model, appraisal theory, and an accountability-oriented reading of targets, reporting, and review. References to Saudi Vision 2030 and the United Nations Sustainable Development Goals connect campus action to authoritative narratives, but alignment can remain ceremonial when it is not translated into actors, resources, indicators, deadlines, and disclosure. Positive evaluation positions universities as leaders and innovators, although evidence ranges from aspiration to quantified outputs and reporting commitments. The institutional pronoun "we" creates solidarity while often concentrating voice at the organizational center. Students, faculty, communities, and partners appear as participants or changemakers, but less often as co-authors with durable decision rights. The article proposes a discursive accountability chain and stakeholder-voice continuum for policies that are measurable, participatory, and open to correction. Constructed examples in Romanized Arabic, with English translations, show how small linguistic choices move a statement from symbolic encouragement to accountable commitment.